Analisis Pengaruh Tarif, Aksesibilitas, Sarana dan Prasarana Terhadap Minat Pengguna Bus Rosalia Indah di Kota Blitar - Faisal, Mochamad; Sulistyowati, Sulistyowati; Amalia, Listiati; Sumantri, Andar Sri; Samekto, Agus Aji; Roesjanto, Roesjanto; Supriyanto, Supriyanto (FEB Universitas Maritim Semarang, 2025)
Abstract. The background of this research is the rampant competition in the bus transportation business which is marked by the increasing number of bus transportation companies in several locations that are even close to each other, which results in customers being faced with a lot of choices. One of the famous transportation services in Blitar City is the Rosalia Indah bus. Ticket sales from PO Rosalia Indah are higher every day compared to other POs, such as PO Harapan Jaya. Therefore, transportation service companies compete with each other to attract consumers. This study aims to determine the effect of tariffs, accessibility, facilities and infrastructure on user interest. The population in this study were Rosalia Indah bus users, the sample of this study was 100 respondents. Sampling technique is nonprobability sampling with the type of sampling, namely incidental sampling. The data analysis used in this study is descriptive analysis and quantitative analysis, the data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package For Social Science (SPSS) version 25. The results of the study by partially testing the t-test hypothesis showed that Rates, Accessibility, Facilities and Infrastructure have a positive and significant effect on increasing user interest. Based on the research results, the regression equation model is Y = 1.821 + 0.424 + 0.263 + 0.178 + . the tariff variable with a regression coefficient of 0.424, the accessibility variable with a coefficient of 0.263, the variable of facilities and infrastructure with a regression coefficient of 0.178. From the regression equation, the tariff variable has the most dominant effect on increasing the number of users with an R2(R Square) test of 0.626 or 62.6% which means that user interest is influenced by tariff variables, accessibility, facilities and infrastructure, and other factors that influence Rosalia Indah bus user interest is 37.4% or 0.374.